Increasing Efficiency in Spare Parts Management: A Case Study of B.T. MINING Co., Ltd. - Sukrasorn, Rutaiphat; Horadee, Jakrapun; Hormjun, Thanaporn; Santisookrat, Surachai (Engineering and Technology Horizons, 2025)
The research aims to enhance the efficiency of spare parts inventory management through the implementation of systematic classification and forecasting techniques. B.T. Mining Co., Ltd. seeks to minimize storage costs, optimize spare parts distribution, and mitigate the risk of shortages. The study began with data collection from the company's maintenance department, focusing on repair records, reimbursements, and storage costs over the past six years, from January 2018 to December 2023. According to the survey, the total spare parts value was 1,381,544.41 baht, prompting the researcher to explore and optimize inventory management. To achieve the research objective, ABC analysis was conducted to classify spare parts based on their utility value. Group A contained nine application values, Group B comprised 13 application values, and Group C included 21 application values. Further classification was applied to Group A, dividing it into two subgroups: parts with a coefficient of variation below 0.25, which were managed by using EOQ model, and parts with a coefficient of variation at least 0.25, which were analyzed along with certain spare parts from Group B. Following the implementation of the optimized inventory management strategy, the total inventory cost was reduced by 43,459.39 baht per year, representing a 56.76% decrease. Previously, excessive procurement of certain spare parts was used as a preventive measure against shortages, leading to high storage costs. The improved inventory management approach successfully addressed this issue, resulting in more efficient and cost-effective operations.